2009
DOI: 10.1186/bcr2242
|View full text |Cite
|
Sign up to set email alerts
|

Triple-negative breast cancers are increased in black women regardless of age or body mass index

Abstract: Introduction We investigated clinical and pathologic features of breast cancers (BC) in an unselected series of patients diagnosed in a tertiary care hospital serving a diverse population. We focused on triple-negative (Tneg) tumours (oestrogen receptor (ER), progesterone receptor (PR) and HER2 negative), which are associated with poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
181
3
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(211 citation statements)
references
References 51 publications
22
181
3
5
Order By: Relevance
“…In our study, ER negative, PR negative and Her2/neu negative receptors constituted 13.2 % of our cases. In previous Indian study revealed 25 % cases of triple-negative breast cancer whereas Western countries have showed 14-30 % of triplenegative breast cancer [9,[31][32][33][34][35]. The negative expressions of triple receptors vary markedly with ethnicity and reported higher in African women as compared to White women [31].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, ER negative, PR negative and Her2/neu negative receptors constituted 13.2 % of our cases. In previous Indian study revealed 25 % cases of triple-negative breast cancer whereas Western countries have showed 14-30 % of triplenegative breast cancer [9,[31][32][33][34][35]. The negative expressions of triple receptors vary markedly with ethnicity and reported higher in African women as compared to White women [31].…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence was higher than that reported in white patients (range, 10%-13%) but was closer to the prevalence reported in African-American patients (range, 23%-30%). 14,30 Few studies have been performed on Hispanics living in the United States. In a small study of 46 patients, the prevalence of TNBC was 10%, 14 although this low prevalence may not be representative because of the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…14,30 Few studies have been performed on Hispanics living in the United States. In a small study of 46 patients, the prevalence of TNBC was 10%, 14 although this low prevalence may not be representative because of the small sample size. In a subsequent study of 255 patients with TNBC, 49 patients (19.2%) were Hispanic Americans.…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries, the majority of the patients have negative lymph nodes. 8,9 Previous Indian studies also have documented a higher proportion of positive axillary nodes at diagnosis.…”
Section: Discussionmentioning
confidence: 93%